Development of fermentation parameters of milk-fat mixtures in the production of sour cream product with phytosterols - Honcharov, Denys; Tkachenko, Nataliia; Nikolaieva, Veronika (Technology audit and production reserves, 2021)
The object of research is a sour cream product with the addition of phytosterols in terms of the finished product from 0.141 to 1.710 g/100 g of product. One of the most problematic places when using phytosterols is their extremely low solubility in water and fats. There are several ways to add phytosterols to foods. Direct application is represented by suspensions of phytosterol nanoparticles. To improve the solubility in water, phytosterols are converted into the form of glycosides. To improve the solubility in fats and oils, phytosterols are converted into fatty acid ethers. An important issue in the development of fermented milk products is the effect of phytosterols on the homogeneity of the system, the fermentation process, the final properties of the product. During the study, the introduction of pre-esterified phytosterols as a substitute for milk fat with a melting point of 32–34 °C to milk-fat mixtures. Milk-fat mixtures of various compositions were fermented with the study of acidity during fermentation. To study the properties of the system, milk fat was replaced by vegetable fat by 25, 50, and 75 %. The content of lactic acid bacteria was determined for the final product and the organoleptic parameters of the product were compared. The results show that when fermenting for 14 hours, the required acidity parameters of pH 4.2 to 4.6, titratable acidity of 76 to 79 °T were achieved at 12 hours. Phytosterols did not harm the fermentation rate, and after the process did not worsen the taste and appearance of the product. This provides the opportunity to obtain a high-quality sour cream product with additional properties. The process of fermentation of sour cream products with phytosterols corresponds to the parameters of the standard sour cream product and sour cream. This provides advantages such as the ability to integrate a new product into the sour cream and sour cream production system without significant changes in technology and equipment.